A Postcolonial Discourse Analysis of Community Stakeholders’ Perspectives on Supporting Urban Indigenous Older Adults to Age Well in Ottawa, Canada - Brooks-Cleator, Lauren A.; Giles, Audrey R. (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2020)
The urban Indigenous older adult population in Canada continues to grow; however, there is a lack of understanding of how non-Indigenous health and social services and Indigenous-specific organizations are responding to and addressing the growth of this population. Therefore, in this research, we conducted a postcolonial discourse analysis of semi-structured interviews with six decision-makers (e.g., managers and directors of health and social services organizations) and seven service providers (e.g., program coordinators and social workers) from Indigenous and non-Indigenous health and social service organizations in Ottawa, Canada, to examine how they produce understandings of supporting urban Indigenous older adults to age well. The participants produced three main discourses: (a) non-Indigenous organizations have a responsibility to support Indigenous older adults, (b) culturally specific programs and services are important for supporting Indigenous older adults to age well, and (c) it is difficult for community stakeholders to support Indigenous older adults to age well because this population is hard to reach. The results demonstrate the complexities and tensions that community stakeholders face in supporting Indigenous older adults to age well within a sociopolitical environment informed by reconciliation and a sociodemographic trend of an aging population.